Conjunctival Provocation Test With Blomia tropicalis - Mourao, Elizabeth Maria Mercer; Rosario, Nelson Augusto (Frontiers in Allergy, 2021)
Background: Conjunctival provocation test (CPT) is used to demonstrate clinical relevance to a specific allergen. Blomia tropicalis (Bt) is a prevalent allergen in tropical regions. Its major allergen Blo t 5 is commonly detected in house dust in Brazil. Patients with allergic rhinoconjunctivitis (ARC) have IgE antibodies to Bt although it may not indicate clinical allergy. Objective: the purpose of this study is to demonstrate the role of CPT in clinical allergy to Bt in allergic conjunctivitis (AC). Methods: CPT was performed in asymptomatic subjects with ARC (n=26) outside the grass pollen season. They had positive skin prick tests (SPT) to Bt and other common inhalant allergens and they were off topical or systemic antihistamines. Standardized allergens were used for CPT (Blo t 5 462.5 ng/mL in 1:1 solution, Alk Abelló). CPT was conducted on a control group of subjects (n=29) without symptoms of ARC and with negative SPT. CPT was performed with progressive doses of allergen solutions in normal saline (1:32, 1:16, 1:8, 1:4, 1:2). CPT with the same allergen dose that elicited a positive reaction was repeated one week later. The protocol was approved by the local Ethics Board and signed informed consent was obtained from all participants. Results: There were 92% (24/26) positive CPT in subjects sensitized to Bt. Significant association was found between SPT and CPT results with Bt (p< .0001). CPT had 92% sensitivity and 100% specificity when compared to SPT results. Positive reactions with the same dose or one immediately higher occurred in 21 out of 22 subjects who repeated TPC one week later. Mild transient nasal symptoms (21/24) were the major side effects of positive CPT followed by moderate periorbital edema which occurred in 41% (10/24). One controlled asthmatic BT-sensitized subject developed wheezing and dyspnea during a positive CPT with Bt that cleared with inhaled albuterol (400 mcg). There were no reactions whatsoever of CPT in nonallergic subjects. Conclusion This study demonstrated that Bt may cause allergic conjunctivitis in our population. In addition, CPT is a safe and reproducible test if standardized allergens are used.